"Explanation of the poem Abdullah Pasha" by Arif Effendi - Verification and study- - Al- Otaibi, Faisal Mohammed Al- Humaidi (Journal of Humanities & Social Sciences, 2020)
The research aims to study and Verify a manuscript book entitled: "Explanation of the poem Abdullah Pasha" by Arif Efendi, a psychological manuscript written in the Ottoman era, which is an explanation of a poem praising one of the prominent figures, the book has linguistic, literary and rhetorical aspects The research was divided into two sections: the first dealt with the author, the poet and the description of the manuscript. The second section focused on the investigation. This research revealed the state of poetry in the Ottoman era, and how it was full of authentic poems that can be considered as good as previous eras